Can Post-Infectious Bronchiolitis Obliterans (PIBO) be Misdiagnosed as Persistent Pneumonia? - Habib, Rahat Bin; Kabir, ARM Luthful (The Journal of Ad-din Women’s Medical College, 2026)
Post-infectious bronchiolitis obliterans (PIBO) is a rare but severe chronic airway disease in children. It usually follows a severe viral lower respiratory tract infection in early life. Persistent inflammation and fibrotic remodeling of the small airways lead to narrowing, air trapping, and progressive loss of lung function. In recent years, reports from countries with high childhood infection burdens, particularly in Asia and Western countries, have drawn more attention to this condition. However, PIBO often remains under-recognized because its symptoms resemble asthma or other chronic lung diseases. This review summarizes available evidence on the epidemiology, risk factors, pathogenesis, clinical features, diagnosis, and management of PIBO in children. Literature was reviewed from published pediatric studies and case series across different regions. Several studies highlight hypoxemia and prolonged mechanical ventilation as strong predictors of disease. Recurrent viral infections, bacterial co-infections, and environmental exposures appear to increase vulnerability. The pathogenesis involves epithelial injury with neutrophildriven in ammation and fibrosis, eventually producing fixed airway obstruction. Clinically, affected children present with a chronic cough, wheeze, tachypnea, and persistent hypoxemia that do not respond to bronchodilators. High-resolution computed tomography (HRCT) is considered the most reliable imaging tool, frequently showing mosaic attenuation, bronchiectasis or air trapping. Lung function testing usually confirms irreversible obstruction. Management remains largely supportive. Systemic corticosteroids, azithromycin, and some immunomodulatory approaches have been tried with variable outcomes. What is clear is that earlier recognition and intervention can help slow progression. More collaborative research is still needed before consistent pediatric guidelines can be developed. The Journal of Ad-din Women's Medical College; Vol. 13 (2), July 2025; p 47-50